A Case Study of Bt Cotton in India: The PLC Framework - Kaur, Bhavneet (Indian Journal of Marketing, 2015)
This paper aimed to track the marketing journey of GM (genetically modified) cotton in India. It used the basic concepts like PLC (product life cycle) and 4P’s framework from the marketing theory to make interpretations. The article underwrote the marketing theory by unifying the theoretical concepts with practicality. The scene was set against the backdrop of India which enhances its significance. The paper revealed that many marketing strategies were used for the introduction as well as penetration of GM cotton in our country. It drew a clear picture of various marketing tactics used by the technology promoters of the product to steer ahead on the path of growth. It also pointed out the legal and procedural irregularities present in the approval system for the new entrants. It further emphasized the fact that GM cotton in India has sailed through many ups and downs in its journey. The marketing strategies adopted were a mix of traditional as well as innovative approaches. The thin line difference between being ethical and unethical also got blurred in some instances.